Question

# Solve the system of equations by elimination :

4Y + 2X = - 7

4Y - 12X = 16

Hint:

**HINT:** Perform any arithmetic operation and then find.

## The correct answer is: x=-23/14 and y=(-13)/14

### Complete step by step solution:

Let 4y + 2x = - 7…(i)

and 4y - 12x = 16….(ii)

On subtracting (i) from (ii),

we get LHS to be 4y - 12x - (4y + 2x) = - 12x - 2x = - 14x

and RHS to be 16 - ( - 7) = 23

On equating LHS and RHS, we have -14x = 23

On substituting the value of x in (i), we get

Hence we get

Note: We can also solve these system of equations by making the coefficients of x

to be the same in both the equations.

Hence we get

Note: We can also solve these system of equations by making the coefficients of x

to be the same in both the equations.

### Related Questions to study

### Use Substitution to solve each system of equations :

X = 3Y - 4

2X - 3Y = -2

### Use Substitution to solve each system of equations :

X = 3Y - 4

2X - 3Y = -2

### Identify the segment bisector of 𝑃𝑅 and find 𝑃𝑄.

### Identify the segment bisector of 𝑃𝑅 and find 𝑃𝑄.

### Solve the following by using the method of substitution

Y= 8X-5

Y=

### Solve the following by using the method of substitution

Y= 8X-5

Y=

### Find the value of x + y.

### Find the value of x + y.

### Identify the segment bisector of 𝑃𝑅 and find PR.

### Identify the segment bisector of 𝑃𝑅 and find PR.

### Solve the system of equations by elimination :

4Y + 2X = - 7

2Y - 6x = 8

### Solve the system of equations by elimination :

4Y + 2X = - 7

2Y - 6x = 8

### Find the value of x and the length of AB if B is the midpoint of AC.

### Find the value of x and the length of AB if B is the midpoint of AC.

### Solve the following by using the method of substitution

X = -7Y - 1,

X = -Y + 11

### Solve the following by using the method of substitution

X = -7Y - 1,

X = -Y + 11

### If lines l and m are parallel, find the value of x.

### If lines l and m are parallel, find the value of x.

### If Q is between P and R, then

### If Q is between P and R, then

### Solve the system of equations by elimination :

6X - 9Y = 10

6X + 2Y = 18

### Solve the system of equations by elimination :

6X - 9Y = 10

6X + 2Y = 18

### Use Substitution to solve each system of equations :

Y = -0.5X

2X + 2Y = 5

### Use Substitution to solve each system of equations :

Y = -0.5X

2X + 2Y = 5

### Find the value of x if B is the midpoint of AC

### Find the value of x if B is the midpoint of AC

### 𝑋𝑌 =?

### 𝑋𝑌 =?

### Use Substitution to solve each system of equations :

Y = 2X - 7

9X + Y = 15

Finding the answer to the given linear equation is the act of solving a linear equation. One of the algebraic techniques for solving a system of two-variable linear equations is the substitution approach. As the name suggests, the replacement method involves substituting a variable's value into a second equation. As a result, two linear equations are combined into one linear equation with just one variable, making it simple to solve. As an illustration, let us swap the value of the x-variable from the second equation and the y-variable from the first equation. By solving the problem, we can determine the value of the y-variable. Last but not least, we can solve any of the preceding equations by substituting the value of y. This procedure can easily be switched around so that we first solve for x before moving on to solve for y.

### Use Substitution to solve each system of equations :

Y = 2X - 7

9X + Y = 15

Finding the answer to the given linear equation is the act of solving a linear equation. One of the algebraic techniques for solving a system of two-variable linear equations is the substitution approach. As the name suggests, the replacement method involves substituting a variable's value into a second equation. As a result, two linear equations are combined into one linear equation with just one variable, making it simple to solve. As an illustration, let us swap the value of the x-variable from the second equation and the y-variable from the first equation. By solving the problem, we can determine the value of the y-variable. Last but not least, we can solve any of the preceding equations by substituting the value of y. This procedure can easily be switched around so that we first solve for x before moving on to solve for y.